Pengaruh Corporate Social Responsibility Terhadap Kinerja Keuangan Dengan Good Corporate Governance Sebagai Variabel Moderasi - Fanisa Anggita Putri; Dewi Saptantinah Puji Astuti (Universitas 17 Agustus 1945 Semarang, 2024)
The research conducted aims to test and analyze the effect of corporate social responsibility on financial performance with good corporate governance as a moderating variable in LQ45 companies on the Indonesia Stock Exchange in 2019-2022. The population used, namely LQ45 indexed companies on the Indonesia Stock Exchange, totals 62 companies in 2019-2022. The analysis uses purposive sampling with a total sample used in the study totaling 16 companies in 2019-2022. The research used secondary data in its annual reports and sustainability reports. Linear regression analysis and regression analysis with moderating variables are uses in analyzing data. The research shows that corporate social responsibility has a significantly positive effect on financial performance and good corporate governance cannot moderate the effect of corporate social responsibility on financial performance.